Correlation between "ABO" blood group phenotypes and periodontal disease: Prevalence in south Kanara district, Karnataka state, India - Gurpur Prakash Pai; Mundoor Manjunath Dayakar; Mulki Shaila; Anitha Dayakar (Wolters Kluwer Medknow Publications, 2012)
Background: The correlation between certain systemic diseases and ABO blood group is a well-documented fact. The association between periodontal disease and ABO blood group is not studied in relation to a specific geographic location. Here is a study conducted on a group of patients belonging to South Kanara district of Karnataka state. Materials and Methods: A total of 750 subjects aged between 30and 38 years belonging to South Kanara district were selected on random basis. The study subjects were segregated into healthy/mild gingivitis, moderate/severe gingivitis, and periodontitis group, based on Loe and Silness index and clinical attachment loss as criteria. The study group was further categorized and graded using Ramfjord's periodontal disease index. Blood samples were collected to identify ABO blood group. Results: Prevalence of blood group O was more in South Kanara district, followed by blood groups B and A, and the least prevalent was AB. The percentage distribution of subjects with blood groups O and AB was more in healthy/mild gingivitis group (group I) and moderate/severe gingivitis group (group II), while subjects with blood groups B and A were more in periodontitis group III. There was increased prevalence of subjects with blood groups O and AB with healthy periodontium, while subjects with blood groups B and A showed inclination toward diseased periodontium. Conclusion: There is a correlation existing between periodontal disease and ABO blood group in this geographic location. This association can be due to various blood group antigens acting as receptors for infectious agents associated with periodontal disease. This broad correlation between periodontal disease and ABO blood group also points toward susceptibility ofthe subjects with certain blood groups to periodontal disease.